siRNA Has Greatly Elevated Mismatch Tolerance at 3′-UTR Sites - Wei, Na (Public Library of Science, 2012)
It has been noted that target sites located in the coding region or the 3′-untranslated region (3′-UTR) can be silenced to significantly different levels by the same siRNA, but little is known about at what specificity the silencing was achieved. In an exploration of positional effects on siRNA specificity by luciferase reporter system, we surprisingly discovered that siRNA had greatly elevated tolerance towards mismatches in target sites in the 3′-UTR of the mRNA compared with the same target sites cloned in the coding region. Assessment of changes in protein and mRNA levels suggested that the differential mismatch tolerance might have resulted from location-specific translational repression in the 3′-UTR. Ablation of argonaute proteins by AGO-specific siRNAs revealed that the AGO2 had major impact on siRNA silencing activity against sites in both coding region and 3′-UTR, while the silencing of nonnucleolytic AGO proteins (AGO1, AGO3 and AGO4) did not significantly affect silencing of sites in either region. This paper revealed the discovery that the specificity of an siRNA can be affected by the location of its target site.